KONSEP PANDUAN DESAIN PELESTARIAN KAWASAN KESAWAN DI MEDAN - Nasution, Meyga Fitri Handayani; Sahera, Lutfi; Siregar, Mustafa Kamal; Lubis, Hadi Fiqri (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Kesawan area is the one of historical areas in Medan, during the colonial period this area was center of trade and office. Formerly Kesawan area could be found many historical building, but nowadays those buildings are replaced one by one with new building, so in the future feared all those historical building would be lost. Therefore, it needs to conserve Kesawan area by utilizing the architectural potential. This research uses qualitative method with the first stages of the research is collecting data of historical buildings, continued to divide the area based on the Classification of Heritage Buildings, the next stage is conducting area analysis and planning the design of area preservation. The purpose of preservation is to bring about the concept of preservation design guidance of Kesawan area to be an architectural tourism area.